Prenatal genetic counselling: issues and perspectives for pre-conceptional health care in Emilia Romagna (Northern Italy) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: there are many reasons why a couple may seek specialist genetic counselling about foetal risk. The referral for prenatal genetic counselling of women with a known risk factor during pregnancy has many disadvantages. Despite this, 10-20% of women seek counselling when already pregnant.Methods: data on 804 pregnant women out of 2 158 (37.3%) referred for genetic counselling in 2010 to three Clinical Genetic Services were retrospectively analysed. Patients referred only for advanced maternal age were analysed in a separate study.Results: the 804 pregnant women were referred for 932 counselling issues. 325 issues (34.9%) were identified during pregnancy and 607 (65.1%) were pre-existing. 81.2% of Italians compared to 41.8% of the non-Italians (P10% for the unborn child was established.Conclusions: genetic services provide 37.3% of counselling to pregnant women. Referral for genetic counselling during pregnancy can require considerable resources and pose significant ethical and organizational challenges. New models of pregnancy care in the community need to be developed. General practitioners and gynaecologists have an important role in the referral and in the defence of equity of access and a more structured approach to the participation of medical geneticists to primary practice should be considered.